2008
DOI: 10.1534/genetics.107.077040
|View full text |Cite
|
Sign up to set email alerts
|

Recessive black Is Allelic to the yellow Plumage Locus in Japanese Quail and Associated With a Frameshift Deletion in the ASIP Gene

Abstract: The recessive black plumage mutation in the Japanese quail (Coturnix japonica) is controlled by an autosomal recessive gene (rb) and displays a blackish-brown phenotype in the recessive homozygous state (rb/rb). A similar black coat color phenotype in nonagouti mice is caused by an autosomal recessive mutation at the agouti locus. An allelism test showed that wild type and mutations for yellow, fawn-2, and recessive black in Japanese quail were multiple alleles (*N, *Y, *F2, and *RB) at the same locus Y and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
3
45
0
1
Order By: Relevance
“…This is therefore some of the first evidence (see also Hiragaki et al 2008, accompanying article in this issue) for a functional ASIP gene in birds with a role in pigmentation. There are striking similarities to the mouse lethal yellow (A y ) mutation.…”
Section: Discussionmentioning
confidence: 65%
“…This is therefore some of the first evidence (see also Hiragaki et al 2008, accompanying article in this issue) for a functional ASIP gene in birds with a role in pigmentation. There are striking similarities to the mouse lethal yellow (A y ) mutation.…”
Section: Discussionmentioning
confidence: 65%
“…2017 137(1) of this found in Common Quail Coturnix coturnix (Fig. 5) and Japanese Quail (Hiragaki et al 2008). The eumelanistic morphs in different isolated populations of Chestnut-bellied Monarch Monarcha castaneiventris on the Solomon Islands are the result of two different mutations.…”
Section: Melanism and Mc1rmentioning
confidence: 88%
“…However, it is reasonable to assume that a comparable agouti gene is present in birds as well, as many species possess feathers with distinct patterns of both melanin types. Several studies have indicated an avian equivalent of the agouti gene in Japanese Quail Coturnix japonicus (Hiragaki et al 2008, Nadeau et al 2008. So evidence suggests that there is a gene in birds responsible for melanin-type switching, which regulates the distribution of eumelanin and phaeomelanin on each feather.…”
Section: Melanins and Plumage Colorationmentioning
confidence: 99%
“…In mouse, as in many other mammals, the wild-type pigmentation pattern of fur is called Agouti, which is involved in the regulation of pigmentation in animals (Mynatt and Stephens 2001;Rieder et al 2001;Eizirik et al 2003;Wolff 2003;Drogemuller et al 2006;Hiragaki et al 2008;Norris and Whan 2008;Royo et al 2008;Jacobs et al 2016;Zhang et al 2016). The relative amounts of pheomelanin and eumelanin pigments determine the color of skin and hair in animals, including mammals and birds.…”
Section: Introductionmentioning
confidence: 99%